Cortical involvement during myotonia in myotonic dystrophy: an fMRI study. (28th January 2015) - Toth, A.; Lovadi, E.; Komoly, S.; Schwarcz, A.; Orsi, G.; Perlaki, G.; Bogner, P.; Sebok, A.; Kovacs, N.; Pal, E.; Janszky, J.
<x xml:space="preserve">Abstract</x> Objective Myotonic dystrophy type 1 (DM1) is a common adulthood muscular dystrophy, characterized by muscle wasting, myotonia, and multisystemic manifestations. The phenomenon of involuntary muscle contraction during myotonia offers a unique possibility of investigating brain motor functions. This study explores cortical involvement during grip myotonia in DM1. Materials and methods Sixteen DM1 patients were enrolled in the study. Eight patients had apparent grip myotonia, while eight patients did not (control subjects). All patients underwent functional MRI grip task examination twice: prior a warm‐up procedure (myotonia was elicited in patients with apparent grip myotonia) and after a warm‐up procedure (myotonia was attenuated in patients with apparent grip myotonia). No myotonia was elicited during either examination in patients without apparent grip myotonia. Cerebral blood oxygen level‐dependent (BOLD) signals were compared both between groups with and without apparent myotonia, and between pre‐ and post‐warm‐up sessions. Results Significantly higher BOLD signal was found during myotonia phase in patients with apparent grip myotonia compared to corresponding non‐myotonia phase of patients without apparent grip myotonia in the supplementary motor area and in the dorsal anterior cingulate cortex. Significant differences in BOLD signal levels of very similar pattern were detected between prewarm‐up session myotonia phase and post‐warm‐up session myotonia absent phase in the group of patients with apparent grip myotonia. Conclusion We showed that myotonia is related to cortical function in high‐order motor control areas. This cortical involvement is most likely to represent action of inhibitory circuits intending motor termination.